Role of trace elements of mineral waters in their effects on neuro-endocrine-immune complex at female rats - Popovych, Igor; Mysula, Igor; Popovych, Dariya; Mysula, Yuriy; Sydliaruk, Nataliya; Yavorska, Oksana; Zukow, Walery (Journal of Education, Health and Sport, 2021)
Background. Drinking mineral water is one of the ethnopharmacologic factors. Previously, we identified the role of organic carbon and nitrogen of mineral waters in their effects on certain metabolic and neuro-endocrine-immune parameters. The purpose of this study is to clarify the role of trace elements of same mineral waters in their effects on neuro-endocrine-immune complex parameters. Material and methods. Experiment was performed on 48 healthy female Wistar rats 240-290 g divided into 5 groups. Animals of the first group for 6 days administered a single tap water through the tube at a dose of 1,5 mL/100 g of body mass. In the second group we administered the water Naftussya from the Truskavets’ layer (Galychyna, Ukraine), in the third group the water Sophiya of the Truskavets’ field. The rats of the fourth group received the native water from the Hertsa (Bucovyna, Ukraine) field, and the last group received its artificial salt analogue. The day after the completion of the drinking course in all rats HRV, endocrine and immunne parameters were registered. Results. The trace elements (fluoride, bromide, iodide, meta-silicic and orthoboric acids) of the chemical composition of loading fluids determine their effect on the neuro-endocrine parameters by 59%, on the immune parameters by 84%. Conclusion. The trace elements (fluoride, bromide, iodide, meta-silicic and orthoboric acids) of mineral waters play an essential role in their effects on the neuro-endocrine-immune parameters of female rats.